1989
DOI: 10.1159/000261221
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Caries Experience in Permanent Molars in a 15-Year-Old African Population

Abstract: Some epidemiologic studies from Africa report higher DMF values in second than in first molars. It is generally accepted that the maturation of dental enamel influences the susceptibility of teeth to caries. The purpose of the present study was to test the hypothesis that DMF values of second molars will be higher than those of first molars if the first molars have reached a high degree of maturation before being exposed to increased cariogenic challenge. The study was carried out in a group of 15-year-old stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…Accordingly, this study seems to confirm the "meta-analyses" which found no definite time trend in caries prevalence in some African countries [4]. A higher prevalence of caries in the second molars than in the first molars has been reported in African children of this age [14,15,32]. Among Caucasians, the reverse has been found [3,17].…”
Section: Comments On Findingssupporting
confidence: 86%
See 1 more Smart Citation
“…Accordingly, this study seems to confirm the "meta-analyses" which found no definite time trend in caries prevalence in some African countries [4]. A higher prevalence of caries in the second molars than in the first molars has been reported in African children of this age [14,15,32]. Among Caucasians, the reverse has been found [3,17].…”
Section: Comments On Findingssupporting
confidence: 86%
“…Among Caucasians, the reverse has been found [3,17]. Various factors have been suggested to explain the higher prevalence of caries in the second molars in Africans; genetic variation [1], malnutrition during mineralization of the second molars [32], the fissure system [12], tooth cleaning devices [6], and the degree of posteruptive maturation of the two molars when subjected to a cariogenic diet [1,15].…”
Section: Comments On Findingsmentioning
confidence: 99%
“…It has been suggested that this is the re sult of a decrease in caries susceptibility brought about by aging, but firm evidence is lacking [Darling, 1965[Darling, ,1970. Observations of the effect of the war-time diet on dental caries from several European countries have provided some support for the view that lack of refined carbohydrates during the early posteruptive life of teeth may lead to higher caries resistance [Adler, 1957;Toverud et al, 1961;Backer Dirks, 1966, 1969, The same conclusion is reached from observa tions that teeth which are exposed to a traditional primitive diet for some years after eruption before be ing subjected to more cariogenic urbanized diet devel op less caries than when subjected to the cariogenic diet since eruption [Cran, 1959;Johnson and Gjermo, 1989], The estimated mean posteruptive age is given in parentheses. Eruption time is taken to be 18 years for third molars and 10 years for premolars.…”
mentioning
confidence: 99%
“…Sevenyea r -old s 19 4 SPSS program package (9). The caries data for their first molars from this investigation were calmpared with the results from the original Toverud studies (1).…”
Section: Reexamination 1983mentioning
confidence: 99%
“…There are reports indicating that the maturation of young permanent first molars in an environment with low cariogenic challenge increases the resistance of these teeth against caries (8). This observation has recently gained support from a study of African adolescents (9). If this maturation is important for future caries susceptibility, one might expect a lasting decreased caries prevalence of the first molars in the age cohorts who were 7 years old during the war, compared with the preand post-war cohorts.…”
mentioning
confidence: 91%